Elevated plasma phospholipase A2 and platelet-activating factor acetylhydrolase activity in colorectal cancer - Yves Denizot; Véronique Truffinet; Stéphane Bouvier; Alain Gainant; Pierre Cubertafond; Muriel Mathonnet (Mediators of Inflammation)
This clinical study reports that blood levels of the pro-inflammatory mediator platelet-activating factor (PAF) did not change in colorectal cancer patients. In contrast, plasma levels of two enzymatic activities, one implicated in PAF production (i.e. phospholipase A2) and one in PAF degradation (i.e. PAF acetylhydrolase activity) were significantly elevated.